Un Evangeliari col·lectari medieval de la Cartoixa de la Valldemossa - Seguí i Trobat, Gabriel (Miscel·lània litúrgica catalana, 2005)
The manuscript 1 from the Majorca Dioc. Lib. is a Carthusian Evangeliary-Collectary that contains the Gospels and the collects prayed at the end matins on Sundays as well as on feasts and commemorations of the sanctoral. It is written in the Gothic script of about 1400 and comes from the Valldemossa charterhouse, as can be inferred fromt its Carthusian-style sanctoral. It is the first Carthusian liturgical book from the ancient Kingdom of Catalonia-Aragon that has been an object of deep study.